MANAJAMEN SPASTISITAS PALSI SEREBRAL MENGGUNAKAN TEKNIK SELECTIVE PERCUTANEOUS MYOFASCIAL LENGTHENING - Prastiya Indra Gunawan; Muhammad Rizki Darmawan M; Riza Noviandi (NEURONA, 2021)
Cerebral palsy (CP) is a condition of a permanent and non-progressive defect in the brain that occurs at an early age. It interferes with brain development and shows abnormalities in position, muscle tone and motor coordination, and other neurological disorders. ????ecent diagnostic guidelines state that cerebral palsy can be established early. The first step in diagnosing cerebral palsy is identifying risk factors. Intervention in the structure and function of the body is the main domain in managing cerebral palsy. This intervention aims to correct anatomical structural abnormalities that can interfere the body function. Spasticity is the most common anatomical structural abnormality found in cerebral palsy. The Selective percutaneous myofascial lengthening (SPML) technique is helpful as a minimally invasive procedure that treats spasticity with more minor complications than conventional surgical techniques. Keywords: cerebral palsy, selective percutaneous myofascial lengthening, spasticity